ANÁLISE DO EQUILÍBRIO DINÂMICO AOS 4 ANOS DE IDADE DE CRIANÇAS DE ESCOLAS MUNICIPAIS DE EDUCAÇÃO INFANTIL - Delacote, Fernanda B. C.; Maçalai, Tuani R.; Bonamigo, Elenita C. B.; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo